Evidence of underdiagnosis and markers of high blood pressure risk in children aged 6 to 13 years - Jeanne Teixeira Bessa Fuly; Nayara Paula Bermudes Giovaninni; Daniele Gasparini Marcato; Eduardo Roberty Badiani Alves; Jéssica Dutra Sampaio; Leonardo Iezzi de Moraes; Thaís Coutinho Nicola; Julyanna Silva Araújo de Jesus; Everlayny Fiorot Costalonga (Jornal de Pediatria, 2014)
Objective: to estimate the prevalence of high blood pressure (BP) in schoolchildren, as well as the reported frequency of previous measurements of BP in these children, and to identify high BP risk markers in the sample. Methods: this was a cross-sectional study involving 794 children aged 6 to 13 years, enrolled in public elementary schools. A questionnaire was given to parents/guardians, consisting of perinatal, socioeconomic data, and information on previous measurements of BP in these children. Anthropometric measurements included weight, height, waist, hip, and arm and neck circumference, in addition to the three BP measurements. Classification of BP levels was carried out according to current international recommendations, established in 2004. Results: the prevalence of high BP (hypertension or prehypertension) was 7%. Only 21.7% of children had previously undergone BP measurements. The odds ratio of high BP among children with and without overweight was 2.9 (95% CI = 1.7 to 5.0, p < 0.001). None of the anthropometric measurements was superior to the Z-score of BMI as a predictor of high BP. History of hypertension during pregnancy (p < 0.001), prematurity (p = 0.006), maternal hypertension (p = 0.01), and paternal hypertension (p = 0.008) were also correlated with the presence of high BP in children. Conclusions: overweight and family history constitute the main risk markers of high BP in children. The low frequency of BP measurement in children observed in this municipality contributes to the underdiagnosis of the disease, with irreversible consequences for these individuals. Resumo: Objetivo: estimar a prevalência de pressão arterial (PA) elevada em escolares, assim como a frequência relatada de aferição prévia da PA nessas crianças. Identificar marcadores de risco de PA elevada na amostra. Métodos: estudo transversal envolvendo 794 crianças de 6 a 13 anos, matriculadas no ensino público fundamental. Questionário entregue aos pais, com informações perinatais, sócio-econômicas e sobre aferição prévia da PA nas crianças. Avaliação antropométrica: peso, altura, circunferências abdominal, de quadril, braquial e cervical, além das três aferições da pressão arterial. Classificação dos níveis pressóricos conforme as recomendações internacionais atuais, estabelecidas em 2004. Resultados: a prevalência de PA elevada (hipertensão ou pré-hipertensão) foi de 7%. Apenas 21,7% das crianças haviam sido previamente submetidas a aferições de PA. A razão de chances de PA elevada entre crianças com e sem excesso de peso foi de 2,9 (IC 95% = 1,7 a 5,0, p < 0,001). Nenhuma das medidas antropométricas foi superior ao Z de IMC como preditor de PA elevada. Histórico de hipertensão na gestação (p < 0,001), de prematuridade (p = 0,006), hipertensão materna (p = 0,01) e hipertensão paterna (p = 0,008) também se correlacionaram à presença de PA elevada nas crianças. Conclusões: excesso de peso e história familiar configuram como principais marcadores de risco de PA elevada em crianças. A baixa frequencia de aferição da PA observada em crianças deste município contribui para o subdiagnóstico da doença, com consequências futuras irreversíveis para esses indivíduos. Keywords: Arterial hypertension, Children, Obesity, Risk marker, Palavras-chave: Hipertensão arterial, Crianças, Obesidade, Marcador de risco